Validation of the Working Ability, Location, Intensity, Days of Pain and Dysmenorrhea (WaLIDD) Scale in Arabic-Speaking Young Female Adults - Bou Haidar PS; Alam DN; Obeid S; Malaeb D; Dabbous M; Sakr F; El Khatib S; Hallit R; Fekih-Romdhane F; Hallit S (Dove Medical Press, 2024)
Patrick Sami Bou Haidar,1,* Desiree N Alam,1,* Sahar Obeid,2 Diana Malaeb,3 Mariam Dabbous,4 Fouad Sakr,4 Sami El Khatib,5,6 Rabih Hallit,1,7,8,* Feten Fekih-Romdhane,9,10,* Souheil Hallit1,11,12,* 1School of Medicine and Medical Sciences, Holy Spirit University of Kaslik, Jounieh, Lebanon; 2School of Arts and Sciences, Social and Education Sciences Department, Lebanese American University, Jbeil, Lebanon; 3College of Pharmacy, Gulf Medical University, Ajman, United Arab Emirates; 4School of Pharmacy, Lebanese International University, Beirut, Lebanon; 5Department of Biomedical Sciences, School of Arts and Sciences, Lebanese International University, Bekaa, Lebanon; 6Center for Applied Mathematics and Bioinformatics (CAMB), Gulf University for Science and Technology (GUST), Hawally, Kuwait; 7Department of Infectious Disease, Bellevue Medical Center, Mansourieh, Lebanon; 8Department of Infectious Disease, Notre Dame des Secours, University Hospital Center, Byblos, Lebanon; 9The Tunisian Center of Early Intervention in Psychosis, Department of Psychiatry "Ibn Omrane", Razi Hospital, Manouba, 2010, Tunisia; 10Faculty of Medicine of Tunis, Tunis El Manar University Tunis, Tunis, Tunisia; 11Department of Psychology, College of Humanities, Effat University, Jeddah, 21478, Saudi Arabia; 12Applied Science Research Center, Applied Science Private University, Amman, Jordan*These authors contributed equally to this workCorrespondence: Souheil Hallit, School of Medicine and Medical Sciences, Holy Spirit University of Kaslik, P.O. Box 446, Jounieh, Lebanon, Email souheilhallit@usek.edu.lbBackground: Dysmenorrhea, characterized by painful menstrual cramps, significantly impacts the well-being of women globally. Despite its prevalence and adverse effects, dysmenorrhea is often underdiagnosed and inadequately treated. This study aims to validate the Arabic version of the Working ability, Location, Intensity, Days of pain, and Dysmenorrhea (WaLIDD) scale among Lebanese female university students aged 18- 45.Methods: This cross-sectional study, involving 729 participants, utilized a translated WaLIDD scale and the Depression, Anxiety, and Stress Scales (DASS-8).Results: Confirmatory Factor Analysis (CFA) confirmed the one-factor structure of the WaLIDD scale, demonstrating excellent fit indices, with good internal reliability. Concurrent validity analysis revealed significant associations between higher WaLIDD scores and elevated levels of depression, anxiety, and stress. The prevalence of dysmenorrhea in the study was estimated at 7.3%.Conclusion: The study underscores the importance of the WaLIDD scale as a reliable and valid tool for assessing dysmenorrhea among Arabic-speaking populations. The successful validation of the Arabic version facilitates its application in Lebanon and potentially other Arab regions, providing a universal tool to predict and assess dysmenorrhea and its impact. Further research is encouraged to explore the scale's applicability in clinical settings and tailor interventions for improved women's well-being.Keywords: dysmenorrhea, psychometric, scale, Arabic